Soil phosphorus dynamics along a loess–limestone transect in Mihla, Thuringia (Germany)1. Issue 6 (23rd October 2017) - Weihrauch, Christoph; Opp, Christian
Abstract: The distribution of phosphorus (P) along a loess–limestone soil transect were investigated to delineate the spatial variation of the nutrient vertically in the soil profiles and laterally in the landscape. We hypothesized that spatial P patterns result from translocation caused by P mobilization, although P fixation would be expected along the slope. To depict this, three P fractions clearly differing in solubility were determined. Soil samples were treated with 0.1 M hydrochloric acid (HCl), with 12.1 M HCl, and with aqua regia (AR). In the profiles the spatial P distribution slightly corresponds to the occurrence of different bedrocks and substrata. Thus, a native "P loading" might not primarily explain the spatial P patterns. Especially the strong enrichment of the toeslope with easily soluble P indicates P translocation and prior mobilization. The enrichment is detectable throughout the profiles. Thus, superficial translocation ( e.g ., erosion) cannot sufficiently explain that pattern. Instead, underground processes must be the cause for this. They cause relatively high vertical and lateral variation in the spatial P distribution, e.g ., within soil horizons and substratum layers. Hence, mixed sampling of soil sections might not produce data accurate enough for some kinds of P research and for P management. Also, the lateral P distribution should be detected more precisely prior to fertilization of agricultural land.